Access to Early Generation Seed: Obstacles for Delivery of Climate-Smart Varieties - Cramer, Laura K. (Springer, 2019)
Changing climates in eastern and southern Africa will require farmers to adjust which crop varieties they grow in order to adapt to changing patterns of weather, pests and diseases. Delivering more suitable, climate-smart crop varieties requires well-functioning seed systems in which actors work in harmony across the supply chain. Although a great deal of previous development funding has been used to breed new varieties and to encourage farmers to adopt them, the availability of early-generation seed (EGS) continues to be limited by bottlenecks in the supply chain. These problems are particularly significant for non-hybrid varieties and less-commercialized food crops developed by public-sector institutions. This study uses two contrasting case studies from Kenya to illustrate the importance of making improved bean seed varieties available to farmers. The first case study documents a successful instance of EGS transfer, whereas the second highlights the types of barriers that can prevent successful variety adoption. Improved coordination among system actors is necessary to reduce the barriers surrounding EGS provision and production, and thereby strengthen climate-adaptive and adaptable seed systems.